2017
DOI: 10.1364/oe.25.018230
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-wave spotlight imager using dynamic holographic metasurface antennas

Abstract: Computational imaging systems leverage generalized measurements to produce high-fidelity images, enabling novel and often lower cost hardware platforms at the expense of increased processing. However, obtaining full resolution images across a large field-of-view (FOV) can lead to slow reconstruction times, limiting system performance where faster frame rates are desired. In many imaging scenarios, the highest resolution is needed only in smaller subdomains of interest within a scene, suggesting an aperture sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Combining the holography concept with the reconfigurable metasurface will further allow dynamic beamsteering capabilities, without the need of mechanical moving parts [49][50][51][52][53][54][55][56][57]. In 2013, the Kymeta Corporation has demonstrated an active metasurface antenna used for bi-directional high-speed internet connectivity [49].…”
Section: Principle Of Holographic Antennasmentioning
confidence: 99%
“…Combining the holography concept with the reconfigurable metasurface will further allow dynamic beamsteering capabilities, without the need of mechanical moving parts [49][50][51][52][53][54][55][56][57]. In 2013, the Kymeta Corporation has demonstrated an active metasurface antenna used for bi-directional high-speed internet connectivity [49].…”
Section: Principle Of Holographic Antennasmentioning
confidence: 99%
“…This attribute partly responds to the problem of reconstructing space-frequency signals in the radiating aperture from a limited number of measured frequency information. The second constraint that needs to be addressed is the replacement of this extremely simple yet inefficient equalization operation with a matrix approach that can be solved by means of various pseudo-inversion techniques, which may be direct such as the Tikhonov regularization [ 12 ] or the truncated singular value decomposition [ 23 ], or iterative such as least squares-based techniques [ 16 , 30 ] or the generalized minimal residual method [ 17 , 31 ]. Using the sparsity properties illustrated above, this reconstruction is carried out in the time domain, working on the expression of the measured signal according to those received in the radiating aperture, filtered by propagation in the computational imaging component.…”
Section: Theoretical Principle Of a Sparsity-based Time-domain Sigmentioning
confidence: 99%
“…The constraint is thus pushed back into the digital layer where the formulation and resolution of inverse problems represent new challenges that can make these solutions competitive. It has been demonstrated that such systems can be based on the use of electrically large cavities connected to conventional antenna arrays [ 11 , 12 , 13 ], on the use of metasurfaces encoding information directly in the radiating aperture [ 14 , 15 , 16 ], or even on hybrid solutions of leaky cavities that demonstrate interesting performance in many imaging modalities [ 17 , 18 , 19 ]. Connections can also be made with earlier systems based on the use of frequency scanning antennas whose radiation patterns can encode a sum of information relative to the position of a target into a reduced number of signals [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of Fresnel focusing enables the antenna radiated fields to be focused at a defined spot in the Fresnel region of the antenna, leading to increased field intensities at the focused region. This capability has been shown to hold significant potential in several emerging applications, such as near-field imaging [7], non-destructive testing [8], and wireless power transfer [9].…”
Section: Introductionmentioning
confidence: 99%